Genetic resources, justice and reconciliation : Canada and global access and benefit sharing - Oguamanam, Chidi, 1965- (Cambridge : Cambridge University Press, 2019)
When the oral history of a medicinal plant as a genetic resource is used to develop a blockbuster drug, how is the contribution of indigenous peoples recognized in research and commercialization? What other ethical, legal, and policy issues come into play? Is it accurate for countries to self-identify as users or providers of genetic resources? This edited collection, which focuses on Canada, is the result of research conducted in partnership with indigenous peoples in that country, where melting permafrost and new sea lanes have opened the region's biodiversity, underscoring Canada's status as a user and provider of genetic resources and associated indigenous knowledge. This work is an important resource for scholars, corporations, indigenous peoples, policymakers, and concerned citizens as Canada and other countries take on the implementation of Access and Benefit Sharing policies over genetic resources and associated indigenous knowledge. This book is also available as Open Access.
Title from publisher's bibliographic system (viewed on 04 Jan 2019).
Keywords: Germplasm resources -- Canada; Medicinal plants -- Research -- Canada; Traditional medicine -- Canada; Indigenous peoples -- Legal status, laws, etc. -- Canada; Oral history -- Canada